Um gerenciador de pacotes de aplicações para redes definidas por software - MENDES, Dângelo Wesley Oliveira (2023)
The paradigm of Software-Deﬁned Networking (SDN) has been investigated as the most promising solution to the current ossiﬁcation of the Internet problem, since it proposes the decoupling of data plane and control plane, providing greater programmability to networks. However, there are currently no open tools that promote the application management for SDN controllers, similarly there are no standardization to packaging it. For this reason, in this work will be presented a solution called Software Package Manager for SDN Applications - SPM. This tool deﬁnes a method for packaging applications SDN, in order to make their practical the control path management of programmable networks, from the use of APIs that automates the installation, update and removal of same which are distributed through a Web repository of these packages. For validation of this work was selected POX controller, from which it was possible the composition of a database for the SPM tool can select the information it need to manage applications in this controller. Throughout the text will be presented the relation of this work with the elements of SDN control plane as well as demonstrated the similarity of this proposal with the package management on GNU/Linux. Finally it will be detailed the solution given by the SPM tool and presented the results of this implementation.